Asymmetric Reconnection Within a Flux Rope‐Type Dipolarization Front. Issue 1 (8th January 2020) - Marshall, A. T.; Burch, J. L.; Reiff, P. H.; Webster, J. M.; Torbert, R. B.; Ergun, R. E.; Russell, C. T.; Strangeway, R. J.; Giles, B. L.; Nakamura, R.; Hwang, K. ‐J.; Genestreti, K. J.
Abstract: On 8 September 2018, at nearly 14:51:30 UT, the Magnetospheric Multiscale (MMS) spacecraft encountered an electron diffusion region near the center of a flux‐rope type dipolarization front. The observed signature of the magnetic field in geocentric solar ecliptic included a bipolar B z coinciding with a peak in B y and |B | as is typical for a flux rope. At the same time, all three spacecraft with available plasma data observed a decrease in density and an increase in temperature over ion scales near the reversal in B z . These ion‐scale changes are expected in a dipolarization front. The three spacecraft with available electron plasma data also observed clear evidence of electron‐scale reconnection just after the B z reversal including ideal magnetohydrodynamics violation, a large out‐of‐plane current, a large j · E ′ energy conversion, and crescent‐shaped electron velocity distributions. This is the first time reconnection has been observed near the center of a flux rope on an electron‐scale during such an event, and MMS was likely very close to the reconnection X‐line. Key Points: MMS observed an earthward propagating flux rope‐type dipolarization front in the near‐Earth magnetotail Electron‐scale magnetic reconnection happened near the center of the structure The X‐line motion was such that MMS1 and MMS2 passed through the inner EDR